External and internal loads of transition games are affected by the presence of an opposing team and their initial positions - Asian-Clemente, J. A.; Asín-Izquierdo, I.; Requena, B.; Galiano, C. (Journal of Human Kinetics, 2025)
The objectives of this study were to compare the external and internal loads of transition games (TGs) without the opposition and TGs with different types of the opposition, and to assess their impact on a series of speed and strength tests. The external and internal loads of 18 young professional players (age: 14.79 ± 0.18 years; body height: 171.9 ± 6.5 cm; body mass: 62.1 ± 7.5 kg) were monitored in three TGs: 1 vs. 0 (no opposition; striker vs. goalkeeper), 1 vs. 1Front (defender between the goal and the striker), and 1 vs. 1Behind (defender behind the striker). Peak velocity (PeakV), distance covered (DC) above 24.0 km·h-1, 21.0-23.9 km·h-1, 18.0-20.9 km·h-1, 13.0-17.9 km·h-1, accelerations and decelerations above 2.5 m·s-2 and below -2.5 m·s-2 as well as the rate of perceived exertion (RPE) were obtained. Before and after each TG, vertical jump performance and sprint ability were assessed. PeakV and DC =24 km·h-1 differed among drills, showing superior outcomes in the 1 vs. 1Behind format. DC 21-23.9 km·h-1 showed significant differences among drills, with larger distances covered in the 1 vs. 0 format. The number of accelerations-decelerations was significantly different among drills. RPE response differed among drills, with larger values for 1 vs. 1Behind and 1 vs. 1Front formats. All post tests showed an effect on time response without significant group interaction. The 1 vs. 1Behind and 1 vs. 0 formats induce higher values for high speed, sprint and accelerations than the 1 vs. 1Front format, which shows better performance in decelerations.